Positioning undergraduate teaching and learning assistants as instructional partners - Jardine, Hannah Elizabeth (International Journal for Students as Partners, 2020)
Undergraduate teaching and learning assistants (UTLAs) can help to implement student-centered learning and collaborate with faculty as instructional partners. Researchers have documented the benefits of student-faculty instructional partnerships, but additional research is necessary to better understand how UTLA-faculty partnerships are established and sustained. In this study, I explored how UTLAs are positioned in interactions with faculty for two undergraduate courses at a large, public research institution over the Fall 2018 semester. This in-depth examination revealed UTLAs may be positioned as students, informants, consultants, co-instructors, or co-creators. Positioning of UTLAs changed moment-by-moment, and the different positions were not always mutually exclusive. Thus, UTLA-faculty partnerships are complex and dynamic; even when ranking or characterizing partnerships broadly, considering variety and fluidity in positioning may help uncover the nuances behind different partnerships. This research provides insight into the interactions of collaborative UTLA-faculty instructional partnerships and the factors that may affect those interactions.